Root Formation Response of Oil Palm (Elaeis guineensis Jacq.) to Naphthaleneacetic acid (NAA) and Indole-3-butyric acid (IBA) under In Vitro Condition - Ilham, Muhammad; Ernayunita, Ernayunita; Rahmadi, Hernawan Yuli (Akademi Komunitas Perkebunan Yogyakarta, 2025)
The root system of oil palm (Elaeis guineensis Jacq.) is a critical component for plant growth. Roots play essential roles in water and mineral absorption, providing structural support, storing energy, and facilitating interactions between plants and microorganisms. In tissue culture, root initiation is one of the key parameters for the successful formation of plantlets. This study aims to analyze the response of growth regulators in inducing roots and increasing the percentage of root formation in oil palm plantlets in vitro using 1-naphthaleneacetic acid (NAA) and indole-3-butyric acid (IBA). The methods included plant material preparation, root growth medium preparation, treatment media preparation, inoculation and incubation, and data analysis. The experimental design employed a Completely Randomized Design (CRD) with nine treatments and one control, each repeated seven times, resulting in 70 experimental units. The data were analyzed using ANOVA, followed by further testing with DMRT at a 5% significance level. The results showed that NAA and IBA positively influenced root formation in oil palm plantlets. A single NAA treatment effectively stimulated root elongation and reduced the time required for root emergence. The combination treatment of 1 mg/L NAA + 2 mg/L IBA produced a higher number of roots in the plantlets.